Design and fabrication of chair from hybrid banana pseudo-stem/glass fibre reinforced polyester composite - Khamis, M. I. H.; Salit, Mohd Sapuan; Zainudin, Edi Syams; Wirawan, Riza; Baharudin, B. T. Hang Tuah (2009)
A study chair has been designed and fabricated using combination of conventional material and natural fibre composite. The seat and the backrest of the chair were made from a hybrid of banana pseudo-stem and glass fibre reinforced polyester composite while the chassis was made from stainless steel. Five concepts have been developed and the selected concept was further enhanced to achieve both ergonomic and aesthetic design. Hand lay-up method was used to fabricate the composite parts of the chair while the chassis was fabricated using commercial manufacturing process. The aesthetic value and mechanical properties make the hybrid of banana pseudo-stem and glass fibre reinforced polyester composites suitable for furniture making materials.